Motion Graphic Dalam Mendukung Penyampaian Pesan Game Show Edukasi “Clash Of Champions” - Sanjaya, William (Universitas Komputer Indonesia, 2024)
Motion graphics have functions that allow messages to be delivered efficiently and attractively to the audience.